Phytochemical Screening and Evaluation of Antidiabetic Activity of the Marine Microalgae: Nannochloropsis Sp.: Life Sciences-Marine Biology for Medical Therapy - Deepa P. K; Subramanian A; Manjusha W.A. (International Journal of Life Science and Pharma Research, 2022)
Diabetes mellitus is a metabolic disorder and is one of the major challenges on health of people all over the world. The phytochemicals of various marine algae are found to possess antioxidant, anti-inflammatory and anti-diabetic properties. Microalgae are photosynthetic organisms that produce oxygen and are capable of producing beneficial secondary metabolites. The bioactive metabolites like pigments, phenolics, amino acids, polyunsaturated fatty acids etc. produced by them have a positive effect on human health. In the present investigation, the marine microalgae Nannochloropsis sp. was screened for phytochemicals qualitatively and quantitatively. The evaluation of antidiabetic activity was determined against the enzymes such as alpha amylase and alpha glucosidase. The extracts were prepared in five different solvents such as petroleum ether, aqueous, isopropanol, methanol and ethyl acetate. The qualitative analysis for phytochemicals showed the presence of alkaloids, phenols, flavonoids, carbohydrates, proteins, cardiac glycosides, sterols, coumarin and tannins. The maximum total phenolic, flavonoid and sterol content was present in ethyl acetate extract of Nannochloropsis sp. and the values are found to be 42.17 ± 0.12mg GAE/g, 60.23 ± 0.09 mg QE/g, 55.34 ± 0.07 mg cholesterol/g of extract respectively. The ethyl acetate extract showed highest inhibitory effect of 78.52 ±0.56 % (IC50 121.96 µg/ml) on α-amylase and 80.42 ± 0.13 % (IC 50 178.53µg/ml) on α-glucosidase enzyme at a concentration of at 1mg/ml which implies the microalgae possess anti-diabetic property. The results indicate that the phytochemicals present in the microalgae contribute the antidiabetic activity. Hence Nannochloropsis sp. can be applied in pharmaceuticals for the development of antidiabetic drugs which have the benefits over side effects by the use of synthetic drugs.